EFFECTIVE METHODS TEACHING FOR KIDS IN ENGLISH (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article explores effective methods for teaching English to young learners. It emphasizes the importance of a communicative approach, incorporating various techniques to create an engaging and interactive learning environment. The discussion focuses on strategies.  Total Physical Response): Using physical actions to reinforce vocabulary and grammar concepts. Songs and Rhymes: Incorporating music and rhythm to make learning enjoyable and memorable .Games and Activities: Utilizing games to practice language skills in a fun and competitive way .Storytelling and Drama: Encouraging creative expression and language use through storytelling and role-playing. Visual Aids and Technology: Employing visual tools and technology to enhance comprehension and engagement. The article concludes by highlighting the significance of positive reinforcement, individual attention, and a focus on the four language skills (listening, speaking, reading, and writing) in creating effective English language learning experiences for young learners